The Influence of Fintech Literacy and Technology Acceptance on the Intention and Usage Behavior of QRIS in Daily Transactions - Hidayat, Ahmad Rexy; Kartini, Kartini (Journal Development Manecos, 2026)
The rapid growth of digital payment systems has transformed financial transactions worldwide, with the Quick Response Code Indonesian Standard (QRIS) emerging as a key instrument in Indonesia’s transition toward a cashless society. Despite its widespread adoption, disparities in financial technology understanding may influence individuals’ willingness to use QRIS. This study investigates the factors influencing QRIS adoption by extending the Unified Theory of Acceptance and Use of Technology (UTAUT) through the inclusion of fintech literacy as an additional construct. Specifically, the study examines the effects of performance expectancy, effort expectancy, social influence, facilitating conditions, and fintech literacy on behavioral intention, as well as the effect of behavioral intention on actual QRIS usage behavior. A quantitative explanatory research design was employed using survey data collected from 138 active QRIS users. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results reveal that social influence and fintech literacy have significant positive effects on behavioral intention to use QRIS, while behavioral intention significantly influences actual usage behavior. In contrast, performance expectancy, effort expectancy, and facilitating conditions do not significantly affect behavioral intention. These findings suggest that QRIS adoption is increasingly shaped by social dynamics and users’ capabilities to understand and utilize digital financial services rather than by technological considerations alone. The study contributes to the technology adoption literature by demonstrating the importance of integrating fintech literacy into the UTAUT framework in the context of digital payment systems. Furthermore, the findings provide practical insights for policymakers, financial institutions, and fintech providers seeking to enhance digital payment adoption through targeted financial literacy programs and community-based engagement strategies.